"The determinants of entrepreneurship in Tabuk: proposals and solutions " In the light of the pilot projects for 2014 - Khamis, Ahmed Saad Mohamed; Al-Zaher, Abdul Baqi Abdullah (Arab Journal for Sciences and Research Publishing, 2017)
This study aims identifying the obstacles that face entrepreneurs in Tabuk. The study has been covered in three chapters. The first chapter was the theoretical framework of this study whereas it discussed the concepts and basics of entrepreneurship. The second chapter explored the development of the concept of entrepreneurship in the Kingdom of Saudi Arabia. The third chapter discussed the present condition of entrepreneurship in Tabuk to identify the problems and restrains faced by entrepreneurship projects approved by the entrepreneurship Institute in Tabuk in 2014. The study arrived to the following problems and restrains that face entrepreneurship in Tabuk: Problems related to promoting the entrepreneur product or service. Financing problems. Administrative problems. Based on these problems, the study recommends the following: Necessity of providing marketing assistance to entrepreneurs and produce new methods of promoting the products and services. Continue providing a complete financing support that include providing accounting and financial advice. Issue administrative instructions that encourage entrepreneurs to a personal responsibility and follow- up of their business instead of depending on foreign workers in order to enrich their personal experiences. Continue raising awareness among youth and students by organizing related events, festivals and presentations. Establish a unit of entrepreneurship studies or include an academic course that enhances the interest toward entrepreneurship at Tabuk University.
Keywords: Entrepreneurship; Entrepreneurial Projects; Reference Points; Proposals